Four new species of Discomorpha Chevrolat, 1837 (Coleoptera: Chrysomelidae: Cassidinae: Omocerini), with key to Discomorpha s. str. - Borowiec, Lech (Zootaxa, 2006)
The following new species of Discomorpha s. str. (Coleoptera: Chrysomelidae: Cassidinae) are described: Discomorpha howdenorum sp. nov. (Venezuela), Discomorpha atahualpai sp. nov. (Peru), Discomorpha putamayoensis sp. nov. (Peru), and Discomorpha giganteensis sp. nov. (Colombia). Colour photos of the dorsal and lateral habitus of all new species are provided. A key to the subgenus Discomorpha s. str. is given. Discomorpha nevermanni (Spaeth, 1928) is transferred from the nominotypical subgenus to the subgenus Vulpia Spaeth, 1913.